Análisis del comportamiento de las exportaciones en las regiones de Loreto San Martín y Ucayali periodo 2016 - 2020 - Zumaeta Tenazoa, Candyda del Rocío (2022)
The thesis aims to analyze the evolution of exports from the Loreto, San Martín and Ucayali regions, period 2016 - 2020; showing the value of traditional and non-traditional exports, the product that had the greatest participation in the structure of exports and the product that was affected by COVID 19, the research is of a descriptive level and a non-experimental longitudinal design, the population It is made up of all the records on exports of the three regions that exist in SUNAT/ADUANAS in the period 2016 - 2020. In Loreto, exports reached the sum of 290.8 million US dollars at FOB value, 226.8 million correspond to traditional products and 60.4 million US dollars to non-traditional products; in San Martin the sum of 677.7 million US dollars, 202.9 million US dollars correspond to traditional products and 474.8 million US dollars to non-traditional products and the Ucayali region only exported non-traditional products for a value of 152.9 million US dollars. Loreto is the only region that suffered a negative impact on all its export products during the pandemic, in San Martín and Ucayali it was the opposite, all its products increased their sales in 2020, which implies that COVID 19 was not an obstacle to grow in exports.